Optimizing clinical guidelines to address antimicrobial-resistant infections: A conceptual framework reflecting stakeholder perspectives - Rhea E. Powell; Sue Felt-Lisk; Arnold Chen; Casey Sullivan (Cambridge University Press, 2023)
Abstract Objectives: Clinical guidelines or guidance is an important tool for preventing and treating antimicrobial-resistant (AMR) infections. We sought to understand and support the effective use of guidelines and guidance for AMR infections. Methods: Key informant interviews and a stakeholder meeting on the development and use of guidelines and guidance for management of AMR infections; the interview findings and meeting discussion informed a conceptual framework for AMR infection clinical guidelines. Participants: Interview participants included experts with experience in guidelines development and physician and pharmacist hospital leaders and antibiotic stewardship program leaders. Stakeholder meeting participants included federal and nonfederal participants involved in research, policy, and practice related to prevention and management of AMR infections. Results: Participants described challenges related to timeliness of guidelines, methodologic limitations of the development process, and issues with usability across a range of clinical settings. These findings, and participants' suggestions for mitigating the challenges identified, informed a conceptual framework for AMR infection clinical guidelines. The framework components include (1) science and evidence, (2) guideline and guidance development and dissemination, and (3) implementation and real-world practice. These components are supported by engaged stakeholders whose leadership and resources help to improve patient and population AMR infection prevention and management. Conclusions: Use of guidelines and guidance documents for management of AMR infections can be supported through (1) a robust body of scientific evidence to inform guidelines and guidance; (2) approaches and tools to support timely, transparent guidelines that are relevant and actionable for all clinical audiences; and (3) tools to implement guidelines and guidance effectively.